Corporate Social Responsibility Model of The Tobacco Industry In Supporting Economic Development In Kudus Regency - Lidya Christina W; Suparnyo Suparnyo; Dwiyana Achmad H; Wahyu Edy Amrulloh; Nandha Surya P; Kathya Irsmi Sufa (Journal of Law, Politic and Humanities, 2026)
This study examines the implementation of Corporate Social Responsibility (CSR) by the tobacco industry as a strategic instrument for supporting regional economic development and enhancing community welfare in Kudus Regency. The object of this research is the CSR practices of tobacco companies and their impact on community empowerment and local economic independence in a region highly dependent on the tobacco sector. This research employs a descriptive qualitative method with a socio-juridical approach. Data were collected through literature review and field research involving local government officials, tobacco companies, and community beneficiaries. The study also analyzes the conformity of CSR implementation with applicable legal regulations. The findings reveal that CSR implementation by the tobacco industry in Kudus Regency has been conducted in accordance with the legal framework and contributes significantly to community welfare and regional economic development. CSR programs include community empowerment, MSME development, BUMDes training, educational infrastructure improvement, and strengthening of the local economy. The role of local government as a facilitator enhances program effectiveness. In conclusion, CSR in the tobacco industry not only fulfills legal obligations but also functions as a collaborative and sustainable model for regional economic development oriented toward community economic independence.